CLAY MINERAL TYPING IN THE SHALE UNITS OF THE KAISTA AND ORA FORMATIONS OF North IRAQ: IMPLICATIONS FOR DEPOSITIONAL ENVIRONMENTS - Al-Hazaa, S. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This paper reports the results of X-ray diffraction mineralogical and Scanning electron microscopic (SEM) studies of the shale units in the Devonian-early Carboniferous Kaista and Ora formations from northern Iraq. The mineral composition is uniform throughout the studied succession, kaolinite, illite, chlorite, and palygorskite form the main clay mineral assemblage while quartz, feldspar, calcite and dolomite form the non-clay fraction of the studied shales. Kaolinite dominates over illite in the Kaista shale, whereas, illite and chlorite with common palygorskite dominate over kaolinite in the Ora shale. The clay mineral assemblage is largely of detrital origin and indicates rather cool and/or dry climatic conditions favouring mechanical erosion of the source rocks. Palygorskite is of authigenic origin in evaporative conditions mostly in the subtidal Ora shales.